(untitled) (World Bulletin of Social Sciences, 2022)
This article is devoted to the study of the soundness of the audience of the radial type in the quality management of the learning process in the acquisition of knowledge trained in education. As well as determining the coefficient of the degree of sounding by the levels of location of trainees in the audience.